Off-limits - Yoon, Helen (2021)
Dad's office is off-limits--which only makes it more intriguing to his curious young daughter. As soon as she sees an opening, she sneaks in to have a look around. After all, there's no harm in just looking, right? What she discovers is a magical wonderland of sticky tape, paper clips that make glorious strands, and a kaleidoscopic array of sticky notes. Who could possibly resist playing with those? In a joyful ode to office supplies, Helen Yoon leads a celebration of just-for-once breaking the rules--and offers a final, funny nod to adults who harbor a similar urge
1.4
Keywords: Office equipment and supplies -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Home offices -- Juvenile fiction; Curiosity -- Juvenile fiction; Conduct of life -- Juvenile fiction; Imagination -- Juvenile fiction; Humorous stories; Realistic fiction